Предмет: Алгебра,
автор: Апукеззз
Упростите выражения:
(2m²+3n)(4m⁴-6m²n+9n²)-28n⁶
(5с-2p²)(25с²+10cp²+4p⁴)-126c³
Ответы
Автор ответа:
0
1) (2m²+3n)(4m⁴-6m²n+9n²)-28n⁶ = 8m^6 -12m^4n + 18m^2n^2 + 12m^4n - - 18m^2n^2 + 27n^3 - 28n^6 = 8m^6 + 27n^3 - 28n^6 = 8m^6 + n^3(27 - 28n^3)
2) (5с-2p²)(25с²+10cp²+4p⁴)-126c³ = 125c^3 + 50c^2p^2 + 20cp^4 - 50c^2p^2 - 20cp^4 - 8p^6 - 126c^3 = -c^3 - 8p^6 = - (c^3 + 8p^6)
2) (5с-2p²)(25с²+10cp²+4p⁴)-126c³ = 125c^3 + 50c^2p^2 + 20cp^4 - 50c^2p^2 - 20cp^4 - 8p^6 - 126c^3 = -c^3 - 8p^6 = - (c^3 + 8p^6)
Похожие вопросы
Предмет: Литература,
автор: dbro777
Предмет: Русский язык,
автор: lanchik20190104
Предмет: Математика,
автор: gfbghn
Предмет: Математика,
автор: Аноним